Evaluasi Geometrik Jalan Pada Ruas Lanosangia – Wantulasi Kab. Buton Utara (Sta. 2+600 – 5+000) - Irwan Lakawa; Muzammil Makmur; Randa Pratama (Sultra Civil Engineering Journal (SCiEJ), 2026)
This study is entitled “Geometric Evaluation of the Lanosangia–Wantulasi Road Section, North Buton Regency (Sta. 2+600–5+000).” Land transportation plays a strategic role in supporting economic growth; therefore, road geometric design must meet technical standards to ensure safety and comfort. This study addresses the issue that several road segments do not fully comply with geometric standards, particularly in terms of sharp curves and steep gradients. The objective of this research is to evaluate the existing geometric conditions, including horizontal alignment, vertical alignment, and cross-sections, based on the Guidelines for Geometric Design of Roads (PDGJ 2021) issued by the Directorate General of Bina Marga. A quantitative descriptive method was applied by comparing field data with applicable standards. Primary data were collected through field surveys using Geodetic/RTK measurements, while secondary data were obtained from related agencies. Data analysis was conducted using Digital Application Road to model alignments and calculate geometric parameters. The results show that the horizontal alignment consists of Spiral–Circle–Spiral (SCS) and Full Circle (FC) curves. Several vertical alignment segments have gradients exceeding 10%, although the overall terrain is classified as flat. The Stopping Sight Distance (SSD) meets safety standards. However, not all geometric elements comply with PDGJ 2021. This study provides recommendations to optimize road design qualit.